Efektivitas Lama Perendaman Ekstrak Bawang Putih dan Pemberian Pupuk Cangkang Kerang terhadap Pertumbuhan Stek Tanaman Mawar (Rosa Hybrida L.) - Utomo Relmana Tarigan; Najla Lubis; Desi Sri Pasca Sari Sembiring (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This study aims to determine the effectiveness of the duration of soaking garlic extract and the provision of shell fertilizer on the growth of rose plant cuttings (Rosa hybrida L). This study used a Factorial Randomized Block Design (RAK) method consisting of 2 factors with 48 plots, namely: The first factor is the duration of soaking garlic extract given the symbol "A" which consists of 4 levels of treatment A0: without soaking, A1: 40 minutes, A2: 80 minutes, A3: 120 minutes The second factor is the provision of shell fertilizer given the symbol "B" which consists of 4 levels of treatment B0: 0 g / polybag, B1: 50 g / polybag, B2: 100 g / polybag, B3: 150 g / polybag. So there are 16 combinations consisting of 3 replications. The parameters observed in this study are the age of shoot emergence, number of leaves, shoot length, number of leaves, leaf length, and percentage of survival. The results of the study showed that the duration of soaking garlic extract and the application of shellfish fertilizer on the growth of rose cuttings (Rosa hybrida L). The results of this study showed that the duration of soaking garlic extract and the application of shellfish fertilizer had no significant effect on all observed parameters.